The impact of profitability and leverage towards stock returns on food and beverage firms listed in indonesia stock exchange period of 2012 – 2014 - Ghoffur, Fadhel; Murtaqi, Isrochmani (The Indonesian Journal of Business Administration, 2018)
Abstract. Indonesia has become the most commercially attractive segment in the consuming class. Indonesia has grown consistently over the past ten years. The consumer goods industry has changed because of economic conditions, changing technology consumers who are more empowered. Cullinary is in great demand in all circles (age, gender, etc). This would be a good opportunity for entrepreneur to start new business in manufacturing in food and beverage. Therefore, this research investigates the impact of profitability and leverage towards stock returns on food and beverage firms listed in IDX period of 2012-2014. This investigation would probably as a reference for entrepreneurs who like to start their own new business. This research find the probability (ROA, ROE, and NPM) and Leverage (DER) as an independent variables, have statistically significant at ? = 10% towards SR as a dependent variable. The relationship among independent variables have various impact on SR. This research stated that, DER has the most impact on SR negatively, and the rest consecutively are negative ROA, positive NPM, and positive ROE. However, the samples are abnormal distributed. For further research, the Author recommends to conduct the advanced of this result, because these political, economic, social cultural, and technology as a macro environment indicators would give an impact dynamic result.Keywords: Return on Asset, Return on Equity, Net Profit Margin, Debt to Equity Ratio, Stock Returns, Consumer Goods, Food and Beverage